Encapsulation of phenolic compounds by spray drying of Ancellotta and Aspirant Bouchet wines to produce powders with potential use as natural food colorants - Álvarez Gaona, Izmari Jasel (2022)
Fil: Álvarez Gaona, Izmari Jasel. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina